THE DYNAMICS OF FOLK COMMUNICATION IN THE FORMATION OF MARANHÃO'S CULTURAL IDENTITY: A STUDY ON THE TAMBOR DE CRIOULA IN SÃO LUÍS, MARANHÃO (Editora Impacto Científico, 2025)
This study discusses the tambor de crioula as one of the most significant expressions of Maranhão’s cultural identity, analyzing it through the identity, historical, and communicational dynamics that shape this manifestation. It assumes that cultural identity emerges from collective processes of recognition, memory, and belonging, expressed through shared practices, symbols, and traditions. In Maranhão, these elements are strengthened by intense ethnic and cultural diversity and by the vibrancy of popular manifestations, among which the tambor de crioula is central. Based on folk communication theories, the research examines how this tradition articulates knowledge, values, beliefs, and forms of sociability, operating as a community-based communication system. The study uses an exploratory approach supported by bibliographic and documentary sources. Findings indicate that the tambor de crioula, as intangible cultural heritage, constitutes a space of resistance, generational continuity, and reaffirmation of Afro-Maranhão heritage, contributing to identity formation, the preservation of collective memory, and the appreciation of popular culture in the state.DOI: https://doi.org/10.56238/edimpacto2025.090-075